Pengaruh Kompensasi Terhadap Motivasi dan Kinerja Karyawan (Studi Kasus Di PT Satu Satu Coffee Company Saat Pandemi COVID-19) - Ketut Dimas Bayu Sedana D; I Nyoman Gede Ustriyana; A.A.A. Wulandira Sawitri Djelantik (Fakultas Pertanian, Universitas Udayana, 2022)
The most important role for companies to provide compensation to their employees is measured through the performance given by employees along with the motivation they get. One company that applies a motivational process before and after employees do work is PT Satu Satu Coffee Company. The purpose of applying the motivational process before and after employees do work is for employees to improve performance in carrying out optimal tasks. The purpose of this research is to find out how compensation influences the motivation and performance of employees of PT Satu Satu Coffee Company. The population of this study were all employees of PT Satu Satu Coffee Company, totaling 32 people. The number of samples in this study were 32 respondents, using a saturated sampling method (census). Retrieval of data by interviews, documentation and questionnaires where factors are measured by giving a score of 1-5. Data analysis is modeled into the SEM (Structural Equation Modeling) model using a tool in the form of smartPLS.3.0 software. The results showed that employee motivation and performance had a positive and significant effect on employee compensation. The indicator that best reflects compensation is insurance, while the indicator that reflects the least is bonuses. The indicators that best reflect work motivation are physiological needs and social needs, while the weakest indicator in reflecting is the need for self esteem. Based on the results of the analysis carried out, the conclusions that can be put forward in this study are that compensation has a positive and significant effect on the motivation of employees of PT Satu Satu Coffee Company and compensation has a positive and significant effect on the performance of employees of PT Satu Satu Coffee Company. Suggestions that can be given to PT Satu Satu Coffee Company, the company provides bonuses regularly and in accordance with the achievements or achievements of these employees. Companies can also provide opportunities for teamwork so that social needs indicators as indicators that best reflect work motivation factors continue to increase.